Descriptive Study On Teaching Reading To The First Grade OfSMA Al-Islam 3 Surakarta In 2012/2013 Academic Year By UMS Students On The Job Training - Nugroho, Muhammad Agung; , Drs. Djoko Srijono, M.Hum; , Dra. Dwi Haryanti, M.Hum (2013)
This research is to describe the teaching reading conducted by UMS students to the first grade of SMA Al-Islam 3 Surakarta in 2012/2013 academic year. It is conducted to know how the teaching reading implemented by UMS students and the problem faced by them during teaching-learning process. The research is a descriptive research. The writer collets the data by observing teaching-learning process, conducting the interview, and documenting some important data that support to this research. The data are from interview script, field note, syllabus, text book, and lesson plan. The methods of collecting data are observation, interview, and documentation. The techniques of analyzing data are reduction the data, data analysis, display the data, and conclusion and verification. The result of the research: 1) the method on teaching reading used by UMS students are GTM and GBA. 2) the goal of teaching reading is to help the students in understanding the reading material such as genre text. 3) reading materials that are given to the students are recount text, narrative text, and procedure text. 4) teaching-learning process is implemented by using three phase technique: pre-reading, whilst-reading, and post-reading. Two students on the Job Training use GTM with applying translation, previewing, and repetition in the classroom activity. One students on the Job Training use GBA with applying BKOF, MOT, JCOT, and ICOT. 5) teaching media used by students on the Job Training are text book "Look A Head1" published by Erlangga, copied texts taken from internet, English dictionary, and white board. 6) teaching evaluation is giving the exercise such answering question related the material by written or oral, students' assignment, and making text independently. Type of the exercise is the multiple choice and essay. 7) problems faced by UMS students on the Job Training are inability to conditioning the class, limited vocabulary by students, limited media, and the methods used by students on the Job Training are less creative.